Assessing relevant climate data for agricultural applications - Ramírez Villegas, Julián Armando; Challinor, Andrew J. (2014)
Data: Data tables with results of assessment of skill of CMIP3 global climate models as well as interpolation skill of WorldClim Study: Here we performed a review of relevant aspects in relation to coupling agriculture climate predictions, and a three-step analysis of the importance of climate